Carrier gas effects on aluminum-catalyzed nanowire growth. (22nd February 2016) - Ke, Yue; Hainey, Mel; Won, Dongjin; Weng, Xiaojun; Eichfeld, Sarah M; Redwing, Joan M
Abstract: Aluminum-catalyzed silicon nanowire growth under low-pressure chemical vapor deposition conditions requires higher reactor pressures than gold-catalyzed growth, but the reasons for this difference are not well understood. In this study, the effects of reactor pressure and hydrogen partial pressure on silicon nanowire growth using an aluminum catalyst were studied by growing nanowires in hydrogen and hydrogen/nitrogen carrier gas mixtures at different total reactor pressures. Nanowires grown in the nitrogen/hydrogen mixture have faceted catalyst droplet tips, minimal evidence of aluminum diffusion from the tip down the nanowire sidewalls, and significant vapor–solid deposition of silicon on the sidewalls. In comparison, wires grown in pure hydrogen show less well-defined tips, evidence of aluminum diffusion down the nanowire sidewalls at increasing reactor pressures and reduced vapor–solid deposition of silicon on the sidewalls. The results are explained in terms of a model wherein the hydrogen partial pressure plays a critical role in aluminum-catalyzed nanowire growth by controlling hydrogen termination of the silicon nanowire sidewalls. For a given reactor pressure, increased hydrogen partial pressures increase the extent of hydrogen termination of the sidewalls which suppresses SiH4 adsorption thereby reducing vapor–solid deposition of silicon but increases the surface diffusion length of aluminum. Conversely, lower hydrogen partial pressures reduce the hydrogen termination and also increase the extent of SiH4 gas phase decomposition, shifting the nanowire growth window to lower growth temperatures and silane partial pressures.